2016
DOI: 10.1002/gj.2876
|View full text |Cite
|
Sign up to set email alerts
|

Multistage dolomitization in the Qal'eh Dokhtar Formation (Middle‐Upper Jurassic), Central Iran: petrographic and geochemical evidence

Abstract: The late Jurassic Qal'eh Dokhtar Formation lithologically comprises three parts, from bottom to top, a lower sandstone unit, middle shale unit and an upper carbonate unit, which extend in a N–S direction over a wide area to the east of the Shotori Range and west of the Lut Block (Central Iran). This succession was deposited on a mixed carbonate–siliciclastic ramp. Carbonate rocks of the Qal'eh Dokhtar Formation vary from undolomitized, to partly dolomitized, to completely dolomitized. Field observations from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Likewise, the presence of limpid cortex indicates the existence of slow replacement phases without the incorporation of impurities from the original sediment or overgrowth phases (syntaxial cementation) on the dolomite cores [60,61]. The δ 18 O values of dolomites reflect the isotopic composition and temperature of dolomitizing fluids [58,[65][66][67][68]. The δ 18 O composition of the ME dolomitic textures is very similar (−2.5-1.0‰ V-PDB), and these values differ from those that would be obtained in dolomites precipitated from Cretaceous marine water (0-3‰, [69]) (Figure 5), so that a primary or early origin for these dolomites can be ruled out.…”
Section: Dolomitization Processmentioning
confidence: 99%
“…Likewise, the presence of limpid cortex indicates the existence of slow replacement phases without the incorporation of impurities from the original sediment or overgrowth phases (syntaxial cementation) on the dolomite cores [60,61]. The δ 18 O values of dolomites reflect the isotopic composition and temperature of dolomitizing fluids [58,[65][66][67][68]. The δ 18 O composition of the ME dolomitic textures is very similar (−2.5-1.0‰ V-PDB), and these values differ from those that would be obtained in dolomites precipitated from Cretaceous marine water (0-3‰, [69]) (Figure 5), so that a primary or early origin for these dolomites can be ruled out.…”
Section: Dolomitization Processmentioning
confidence: 99%
“…It has particularly been suggested that Fe and Mg are released at temperatures >100 °C, presumably up to about 125 °C (Boles and Franks, 1979). Clay min- eral transformations have been interpreted as a major control on dolomitization in argillaceous carbonates (McHargue and Price, 1982;Gregg, 1988;Ali, 1995;Glumac and Walker, 2002) and limestones adjacent to shales (Mattes and Mountjoy, 1980;Gawthorpe, 1987;Srinivasan et al, 1994;Suchý et al, 1996;Sabbagh Bajestani et al, 2018), but also in sandstones (Śliwiński et al, 2016) and volcaniclastic rocks (Zhu et al, 2017). In this case, several lines of evidence support the assumption that illitization of smectite during burial supplied Mg ions for dolomitization of the ribbon rocks, e.g., the selective replacement of argillaceous carbonate layers and the presence of illite (vs. absence of smectite) in the dolostones.…”
Section: Limestone-dolostone Ribbon Rocksmentioning
confidence: 99%
“…Adams and Rhodes (1960) showed that seepage-reflux dolomitization resulted in the formation of dolomite in western Texas. In the last 30 years, a series of other dolomitization has been well documented, such as burial dolomitization (Sabbagh Bajestani, Mahboubi, Al-Aasm, Moussavi-Harami, & Nadjafi, 2016;Wierzbicki, Dravis, Al-Aasm, & Harland, 2006) and hydrothermal dolomitization (Qing & Mountjoy, 1994;Smith, 2006). In addition, microbial dolomitization provides a new implication for dolomite formation (Vasconcelos, McKenzie, Bernasconi, Grujic, & Tiens, 1995;Wright, 1999).…”
Section: Introductionmentioning
confidence: 99%